Relationship between metronidazole metabolism and bactericidal activity. - Chrystal, E J (1980)
It has been suggested that the microbicidal effect of metronidazole is mediated by an intermediate in nitro group reduction. We have found that the addition of Escherichia coli enhances the lethal effect of metronidazole on Bacillus fragilis and suggest that this intermediate may form in one bacteria and kill another. Because acetamide forms during the reduction of metronidazole, we examined the possibility that the same partially reduced intermediate in metronidazole reduction may be both an intermediate in the formation of acetamide and the ultimate reactive form of metronidazole which is responsible for its bactericidal action. Thus, we determined the relationship between bacterial survival and the formation of acetamide when cultures of B. fragilis, Clostridium perfringens, and E. coli were incubated anaerobically in the presence of metronidazole. We found that the log of the early bacterial survival was proportional to the formation of acetamide. The rate of loss of metronidazole was not dependent on the concentration of bacteria in the medium, suggesting that any proposed intermediate formed at a rate which was proportional only to the concentration of metronidazole.